Diálogos entre Mário de Andrade e Francisco Curt Lange: nacionalismo e americanismo musicais nas décadas de 1930 e 1940 - Moya, Fernanda Nunes [UNESP] (2014)
This work aims to discuss both the quest for nationalization of music from folk elements of Brazilian culture undertaken by Mário de Andrade, as well as the musical americanism of the german naturalized uruguayan Franz Kurt Lange / Francisco Curt Lange who preached a cultural integration of the continent by means of this form of art. Both intellectuals created an extensive bibliography and documentation with proposed musical ideals which had as one of the main purposes the cultural emancipation of brazilian, according to Mario, and the emancipation of the american citizen, according to Lange. To do so, both occupy administrative chairs in the cultural area and carry out various actions which converge on their proposals